Identifikasi Karakteristik Siswa Berdasarkan Kemampuan Representasi dan Pembuktian Matematis Menggunakan Pengelompokan K-Means - Maharani, Devy Sagita; Lestari, Karunia Eka (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to identify the characteristics of student groups based on mathematical representation and mathematical proof abilities. The approach in this research is quantitative with descriptive method. The population in this study was 11th-grade students of SMA Negeri 6 Karawang, with a sample of 71 students obtained using a random sampling technique based on the Slovin formula. The data collection technique used was filling out test instruments in the form of description questions. The instrument used consisted of three questions to measure mathematical representation ability and three questions to measure mathematical proof ability. The data analysis technique used was k-means clustering. The results showed that the student group was divided into three clusters. In cluster one, there were 16 students with the characteristics of the student group having a fairly good understanding of mathematical representation problems, but not understanding mathematical proof, so it is recommended to apply the problem posing learning model. In cluster two, there are 18 students with the characteristics of student groups lacking understanding of mathematical representation problems and having a fairly good understanding of mathematical proof problems, so it is recommended to apply the multi-recentacy discourse learning model. In cluster three, there are 37 students with the characteristics of the student group having a good understanding of mathematical representation problems and having a fairly good understanding of mathematical proof, so it is recommended to apply the inquiry-based learning model